The Analysis of Drug-Related Problems (DRPs) in the Therapy of Patients with Chronic Kidney Disease in the Inpatient Installation of X Hospital, Medan - Kukuh Putri Lestari; Husnawati Husnawati; Prasojo Pribadi (Universitas Pahlawan Tuanku Tambusai, 2026)
Chronic kidney disease is a progressive disorder that is often accompanied by complications and requires complex therapy, thus increasing the risk of Drug Related Problems (DRPs). The occurrence of DRPs can affect Clinical Outcomes in patients undergoing hemodialysis. The purpose of this study was to analyze the occurrence of DRPs and its relationship to the Clinical Outcomes of patients with chronic kidney disease in the Inpatient Installation of X Medan Hospital for the period January - December 2025. The method used was a descriptive analytical observation with a retrospective cross-sectional design with medical record data. The study sample was 57 patients who met the inclusion criteria. Data analyzed included patient characteristics, drug use, DRPs occurrence based on the Pharmaceutical Network Europe (PCNE) classification, clinical outcomes including blood pressure, hemoglobin and creatinine. The results of the study showed that the majority of patients were male (56.1%), for the 46-65 age group 59.6%, the most commonly used oats were sodium bicarbonate (52.63%), furosemide (43.86%). The incidence of DRPs in 41 patients (71.9%), with indications not being treated (73.17%), and potential interactions (26.83%). The clinical outcomes of most patients had not reached the therapeutic targets, namely, blood pressure (61.4%), hemoglobin (60.7%), and creatinine (57.9%). The conclusion of this study indicates that the incidence of DRPs in patients with chronic kidney failure is still high, potentially affecting clinical outcomes. Therefore, it is necessary to optimize the role of clinical pharmacists in identifying and monitoring therapy to improve the success of patient therapy.